The Diaries of Frank Hurley 1912-1941 - Dixon, Robert; Lee, Chris John (Anthem, 2011)
This is the first illustrated edition of the diaries kept by Australian-born photographer and film maker Frank Hurley about his work on the Mawson and Shackleton Antarctic Expeditions, his two expeditions to Papua in the 1920s, and his experiences during the First and Second World Wars. Arts, Education and Law No Full Text